STUDY OF THE PHYSICAL AND MECHANICAL PROPERTIES OF HOSIERY PRODUCTS MADE OF RAW MATERIALS WITH DIFFERENT COMPOSITIONS - Jurabayev Nozimjon Nizomiddin o’g’li; Yusupov Sabirjon Abdujabborovich (Modern American Journals, 2025)
During the research, 4 different samples with different compositions were produced on a single-needle 156-needle sock knitting machine of the Chinese company Kejun KJ6F606 model, and their physical and mechanical properties were studied.
Keywords: Socks, cotton, polyester, spandex, KJ6F606